Multi-objective competency-based approach to project scheduling and staff assignment: case study of an internal audit project - Wang, X.; Ferreira, F.; Chang, C. (Socio-Economic Planning Sciences, 2022)
As a project-oriented department, internal audit function plays an important role in internal control and corporate governance. Internal audit managers face a challenging multi-skill project scheduling problem, struggling with giving priority to project efficiency or auditor competency development. Motivated by the dilemma surroundings such settings, we aim to generate an audit project schedule taking auditor competency evolution into account, which has not been addressed in previous studies on auditing. We propose a 4-stage model as a guideline to resolve the problem. In this model, weighted compatibility indicator is developed to measure the auditor competency level and multi-choice goal programming (MCGP) is formulated to find the trade-offs between project efficiency and staff competency improvement. A real case study on internal audit project is presented to illustrate the usefulness of proposed model and its appropriate solution. The results show that competency increment goal can be achieved within the project deadline. This research extends the existing literature on audit project scheduling by explicitly considering competency development based on the learning effect. The proposed MCGP approach also provides an ideal project scheduling and staff assignment plan by avoiding underestimation of aspiration level setting in the decision-making problem. As such, this useful and realistic mathematical model would be of great practical value in the applications of scheduling problem in various industries.